Alleged Medical Negligence in Tubectomy Associated Death: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
A 27-year-old, mother of four children, from rural background visited a government district hospital for permanent birth control under a government programme. She was advised to get admitted for the Laparoscopic Tubal Obliteration which was planned for next day. Accordingly, she got admitted in the morning and was operated in the afternoon and by evening she was discharged in a recovered condition with an advice to come for stitch removal after one week. Unfortunately, she expired on postoperative 7th day at home. A police complaint of wrong treatment was lodged. The autopsy revealed massive intestinal haemorrhage from colonic diverticulum leading to hemorrhagic shock as the cause of death as. After the local inquiry, the complaint was also registered at national human rights commission. Forensic investigation framework along with correlation of cause of death with treatment has been discussed in the light of professional standards.
Keywords: Diverticulosis; Intestinal haemorrhage; Medical negligence; Tubal ligation